ENHANCING FURROW IRRIGATION PERFORMANCE AND WATER PRODUCTIVITY THROUGH BETTER DESIGN AND WATER MANAGEMENT IN A CRACKED SOIL - & Karim, Karim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Furrow irrigation is widely used because of its low cost and energy requirement, but less efficient compared with the pressurized irrigation systems. Management of water resources in Vertisols is more problematic compared to other soil groups. This soil is representing a vast crop production resource and account for a considerable portion of the region under study. The preferential flow has a profound effect on the performance furrow irrigation in cracked soils.  Accordingly, itis of vital importance to select the most appropriate management practices to improve the performance of surface irrigation in these soils. Accordingly, a series of field experiments were conducted over a cracked soil at a research farm located in the outskirt of Sulaimani city during the summer seasons of 2017 and 2018 with furrow lengths in the range of 30 to 70 m. The main objectives were to improve the performance of furrow irrigation and water use efficiency of eggplant by changing furrow shape and length by application different irrigation techniques. The results indicated that irrigation efficiency tended to increase by reducing furrow length, by decreasing available water depletion and by changing the furrow shape. Overall, the applied irrigation treatments can be ranked according to the degree of  their effectiveness  in term of irrigation performance, eggplant fruit yield and water use efficiency as follows: Surge flow > Fixed furrow irrigation > Alternate furrow irrigation > Cutback > continuous flow.